ASSESSMENT OF FRICTION STIR WELDING JOINTS OF AA2017-T4 ALUMINUM BY DISC PRESSURE MECHANICAL TESTS - Djili, Abderrahmane; Bezzazi, Boudjema; Haboussi, Mohamed; Zioui, Nadjet (Journal of Applied Engineering Science, 2023)
Precipitation hardening aluminium alloy sheets AA2017-T4 are welded by FSW on a conventional FSW tool. A macrograph of the cross section of the butt-welded joint shows the classical zones for such welding, namely the nugget zone, the thermo-mechanically affected zone and the heat affected zone. Scanning Electron Microscopy displays a grain refining and a re-formation of the precipitates in the nugget zone. Micro-hardness measurements on the cross-section perpendicular to the welding direction give the standard W-profile of the hardness for such welding, with as expected, the relatively highest value at the joint center (nugget zone). To assess the mechanical performance of the FSW welded joint, the Disk Pressure Test (DPT) is used. It shows a failure pressure for the welded specimen that is 17% lower than the base material. The fracture surface micrographs clearly show a thickness reduction at break that is ~36% higher for the base material than the welding joint and a ductile fracture mode for both specimens.
Keywords: FSW, Aluminium alloy, tensile mechanical test, Disk Pressure Test (DPT)